Sheba the chimp and Skylar. - Boysen, Sarah (Scholastic New York, 1992)
This is about a chimp born to parents who use sign language and who grew up at the Columbus Zoo. She uses sign language to communicate with humans.
Chimpanzees
Chimpanzees
incl.
Keywords: Chimpanzees. -- Zoos. -- Sign Language